Transtorno de estrés post-traumático y su relación con la transformación persistente de la personalidad en los pacientes quemados mayores de 18 años de edad del hospital Regional Isidro Ayora de la ciudad de Loja periodo febrero- julio 2013 - Gordillo Llivigañay, María Gabriela (2014)
The Dysfunction of Post-traumatic Estrés is defined like an intense emotional reaction before an experienced event as unexpected and traumatic, affects to millions of people every year, having as origin diverse causes, among them: the lesions for burns that are caused by physical, chemical or biological agents, causing sequels of emotional type and serious complications as it is the Dysfunction of Estrés Post-traumatic psychological entity that is intimately related with the Personality. In the face of this reality it has felt convenient to carry out the present investigative work of descriptive-statistical type with mixed focus on the Dysfunction of Post-traumatic Estrés and their relationship with the Persistent Transformation of the Personality, for the development of the investigative study you work with 63 patients of the Unit of Burnt of the Regional Hospital Isidro Ayora of the City of Loja, in a period of 6 months. Among the outlined objectives they are: to establish the prevalencia of the Dysfunction of Post-traumatic Estrés epidemically, to identify the relationship with the Persistent Transformation of the Personality and to determine the traumatic factors that influence in their appearance. For the execution of the same ones the Psychological Evaluation was used (Record of Observation, Interviews and Clinical History) and the Psychological Reagents (The Clinical Inventory Multiaxial of Million, MCMI-III, Scale of Trauma of Davidson, Scale of graveness of symptoms of the Dysfunction of Post-traumatic Estrés). Concluded the study was found that a significant quantity of patients presented Dysfunction of Post-traumatic Estrés, you identifies the relationship with the Persistent Transformation of the Personality with the types: Evitativo, Clerk and Paranoid, jointly with the traumatic factors. KEY WORDS: Dysfunction of Post-traumatic Estrés, Personality, Burns